An international multicenter propensity‐score matched and coarsened‐exact matched analysis comparing robotic versus laparoscopic partial liver resections of the anterolateral segments. (27th April 2022) - Kadam, Prashant; Sutcliffe, Robert P; Scatton, Olivier; Sucandy, Iswanto; Kingham, T. Peter; Liu, Rong; Choi, Gi Hong; Syn, Nicholas L.; Gastaca, Mikel; Choi, Sung‐Hoon; Chiow, Adrian K. H.; Marino, Marco V.; et al.
Abstract: Background: Robotic liver resections (RLR) may have the ability to address some of the drawbacks of laparoscopic liver resections (LLR) but few studies have done a head‐to‐head comparison of the outcomes after anterolateral segment resections by the two techniques. Methods: A retrospective study was conducted of 3202 patients who underwent minimally invasive LR of the anterolateral liver segments at 26 international centres from 2005 to 2020. Two thousand six hundred and six cases met study criteria of which there were 358 RLR and 1868 LLR cases. Perioperative outcomes were compared between the two groups using a 1:3 Propensity Score Matched (PSM) and 1:1 Coarsened Exact Matched (CEM) analysis. Results: Patients matched after 1:3 PSM (261 RLR vs 783 LLR) and 1:1 CEM (296 RLR vs 296 LLR) revealed no significant differences in length of stay, readmission rates, morbidity, mortality, and involvement of or close oncological margins. RLR surgeries were associated with significantly less blood loss (50 mL vs 100 ml, P  < .001) and lower rates of open conversion on both PSM (1.5% vs 6.8%, P  = .003) and CEM (1.4% vs 6.4%, P  = .004) compared to LLR. Though PSM analysis showed RLR to have a longer operating time than LLR (170 minutes vs 160 minutes, P  = .036), this difference proved to be insignificant on CEM (167 minutes vs 163 minutes, P  = .575). Conclusion: This multicentre international combined PSM and CEM study showed that both RLR and LLR have equivalent perioperative outcomes when performed in selected patients at high‐volume centres. The robotic approach was associated with significantly lower blood loss and allowed more surgeries to be completed in a minimally invasive fashion. Abstract : This international combined propensity score‐matched and coarsened exact‐matched study by Kadam et al showed equivalent perioperative outcomes of robotic and laparoscopic liver resection in selected patients at high‐volume centers. The robotic approach was associated with significantly lower blood loss and allowed more surgeries to be completed in a minimally invasive fashion.